The therapeutic promise of probiotic Bacteroides fragilis (BF839) in cancer immunotherapy - Peng, Kunwei; Li, Yuqing; Yang, Qijun; Yu, Peijin; Zeng, Ting; Lin, Chuhui; Deng, Yuhong; Chen, Jingqi (Frontiers in Microbiology, 2025)
BackgroundOverwhelming evidence suggests that the gut microbiota modulates tumor response to immune checkpoint inhibitors (ICIs). The probiotic Bacteroides fragilis (BF839) was extensively used in China to improve gut microbiota dysbiosis-related symptoms. We hypothesized that probiotic BF839 could enhance tumor sensitivity to ICIs.MethodsIn the preclinical studies, mice received BF839 orally, PD-1 intraperitoneal injection, or a combination therapy of the two agents. The antitumor effect of BF839 was investigated by assessing the tumor growth and tumor immune microenvironment. Mice fecal samples were collected for 16S rRNA sequencing. Fresh tumor samples were collected for 16S RNA sequencing. The data of 29 patients with advanced solid tumor who received BF839 adjuvant therapy were retrospectively evaluated. The primary endpoint was overall survival (OS).ResultsAmong patients with advanced solid tumors undergoing ICIs and chemotherapy, patients in BF839 long-term adjuvant treatment group had longer OS (p = 0.0101) than the BF839 short-term adjuvant treatment group. In the preclinical studies, we found that monotherapy with BF839 or anti-PD-1 antibody significantly inhibit tumor growth. Interestingly, BF839 worked synergistically with anti-PD-1 antibody and induced tumor regression, mediated by increased CD8+T cell infiltration. Mechanistically, BF839 induced tumor suppression was regulated by the cGAS-STING pathway. 16S rRNA sequencing results of mice fecal samples showed that BF839 treatment increased gut microbiota diversity.ConclusionOverall, our data suggest that BF839 enhanced tumor sensitivity to ICIs through cGAS-STING signaling. In the future, the application of probiotic BF839 to regulate gut microbiota may be a new strategy to enhance the efficacy of ICIs.